Effective Mobilization of Very Small Embryonic-Like Stem Cells and Hematopoietic Stem/Progenitor Cells but Not Endothelial Progenitor Cells by Follicle-Stimulating Hormone Therapy. (9th November 2015) - Zbucka-Kretowska, Monika; Eljaszewicz, Andrzej; Lipinska, Danuta; Grubczak, Kamil; Rusak, Malgorzata; Mrugacz, Grzegorz; Dabrowska, Milena; Ratajczak, Mariusz Z.; Moniuszko, Marcin
Abstract : Recently, murine hematopoietic progenitor stem cells (HSCs) and very small embryonic-like stem cells (VSELs) were demonstrated to express receptors for sex hormones including follicle-stimulating hormone (FSH). This raised the question of whether FSH therapy at clinically applied doses can mobilize stem/progenitor cells in humans. Here we assessed frequencies of VSELs (referred to as Lin − CD235a − CD45 − CD133 + cells), HSPCs (referred to as Lin − CD235a − CD45 + CD133 + cells), and endothelial progenitor cells (EPCs, identified as CD34 + CD144 +, CD34 + CD133 +, and CD34 + CD309 + CD133 + cells) in fifteen female patients subjected to the FSH therapy. We demonstrated that FSH therapy resulted in statistically significant enhancement in peripheral blood (PB) number of both VSELs and HSPCs. In contrast, the pattern of responses of EPCs delineated by different cell phenotypes was not uniform and we did not observe any significant changes in EPC numbers following hormone therapy. Our data indicate that FSH therapy mobilizes VSELs and HSPCs into peripheral blood that on one hand supports their developmental origin from germ lineage, and on the other hand FSH can become a promising candidate tool for mobilizing HSCs and stem cells with VSEL phenotype in clinical settings.